Studies published in indexed journals on lawsuits for medicines in Brazil: a systematic review - Vanessa Santana Gomes; Tânia Alves Amador (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The aim of this systematic review was to identify and characterize articles in indexed scientific journals with quantitative data surveys on administrative or legal proceedings for access to medicines. The SciELO, LILACS, MEDLINE via PubMed, Embase, and Scopus databases were used. We identified 45 articles, of which 17 were selected. The larger studies, each covering between 2,000 and 2,927 lawsuits, were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina, Brazil. Eleven studies specified the type of legal representation, of which six examined cases with public attorneys and five with private attorneys. Only two studies reported whether the lawsuit was individual or class action, and in both the claims were individual. Since the majority of the medicines requested in the lawsuits were medium to high-cost, the review indicates that lawsuits contributed to the incorporation of these drugs into current pharmaceutical care in Brazil.